Seismic design of soft-storey buildings - Ruiz Castillo, Carlo (My University, 2017)
This thesis presents the state-of-the-art on the seismic design and assessment of soft/weak storey buildings, specifically in what regards Building Code's specifications and recommendations for the seismic design of this type of vertical irregularity. A summary of various authors' past research on the topic of buildings with a soft/weak storey irregularity is shown. Afterwards, a short review of the influence of geometric second order effects (\(P\Delta\)) and cyclic degradation of elements in the global stability and collapse evolution of a framed structure with soft/weak storey characteristics is presented, complemented with collapse-assessment methodologies. The theoretical basis required for the definition of a practical criterion to delimit this type of irregularity is investigated, in order to posteriorly develop a design methodology that properly includes the most relevant aspects on the performance of such buildings. Finally conclusions are drawn as to the present state and future state of the topic.
Esta tesis presenta el estado del arte en el diseño y evaluación sísmica de edificios con piso blando/débil, específicamente las especificaciones y recomendaciones de los códigos de construcción a este tipo de irregularidad vertical. Un resumen de estudios previos de diversos autores sobre el tema de edificios con piso/blando débil se muestra. Posteriormente, se muestra una revisión de la influencia de efectos geométricos de segundo orden (\(P\Delta\)) y la degradación cíclica de elementos en la estabilidad global y la evolución del colapso de una estructura a base de marcos con características de piso blando/débil. Se complementa lo anterior con metodologías para evaluar y delimitar el colapso estructural. Se investigan las bases teóricas requeridas para la definición de un criterio práctico para delimitar este tipo de irregular, para posteriormente poder desarrollar una metodología de diseño que incluya los aspectos más relevantes en el desempeño estructural de este tipo de edificios. Finalmente se extraen conclusiones para el estado actual y futuro del tema.
Keywords: Diseño de software sismico; Sismos en edificios; Detección de sismos; Sismos en piso débil en edificios; Sismo en piso débil blando